Hubungan Antara Chronotype dengan Prestasi Belajar Pada Siswa Kelas XI di SMAN 1 Boyolali - Afghaniy, Faisal, dr. Yusuf Alam Romadhon, M.Kes (2017)
Each individual presents significant difference regarding their circadian rhythm preference. Chronotype refers to individual preference in selecting hours of sleep, divided into morning and night type. Currently, chronotype emerges as one of the indicators in assessing the impact of the result of a student's academic achievement. Aim/Objective to prove the correlation between chronotype and student's achievement in class XI of SMAN 1 Boyolali. Analytical observational research with Cross Sectional approach and Purposive Sampling technique. 71 students of class XI of SMAN 1 Boyolali have been selected after considering the restriction criteria. Questionnaire and grades are used as measuring instrument. Data analysis is executed by Chi-Square test using SPSS Program version 23. 29 students (41%) are the respondents whose chronotypes are morning achieve well academically, while 9 students (13%) achieve less than average. On the other hand, 11 students (15%) are the respondents whose chronotypes night achieve well academically, 22 students (31%) achieve less than average. There is correlation between chronotype with the student achievement in class XI of SMAN 1 Boyolali.